Anticancer and Apoptotic Effects of Juglone in Ovarian Carcinoma: An Integrated Computational and Experimental Study - Wu, Mei; Xia, QinJian; Liu, Lihui; Kang, Le (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Juglone, a naturally occurring naphthoquinone, has been recognized for its potential anticancer properties. Recent advances in network pharmacology allow for the systematic elucidation of complex molecular interactions in disease, particularly in oncology. Objectives: This study aimed to integrate network pharmacology, in silico molecular docking and experimental validation to demonstrate the anticancer potential of juglone in OVCAR-3 human ovarian carcinoma cells. Materials and Methods: SwissADME and Pro-Tox 3.0 assessed the physicochemical and toxicological properties of juglone. Protein targets were predicted using the SwissTargetPrediction and Super-PRED servers, while ovarian cancer targets were retrieved from the GeneCards database. Common targets were identified via the Venny online tool and Protein-Protein Interaction (PPI) networks were constructed to reveal key targets and connectivity. Functional annotations and enrichment analyses were conducted using bioinformatics software and GEPIA-2 performed expression analysis of hub genes in tumor versus normal tissues. The identified hub genes were subjected to molecular docking to evaluate non-covalent interactions with juglone. In vitro assays included MTT (3-(4,5-Dimethylthiazol-2-yl)- 2,5-Diphenyltetrazolium-Bromide), Annexin V/PI and flowcytometry for cytotoxicity, apoptosis and cell cycle against OVACAR-3 cells, respectively. Results: SwissADME revealed juglone’s favorable ADME (bioavailability=0.55, high GI absorption, BBB permeability) and Pro-Tox 3.0 confirmed its safety. Target prediction (SwissTargetPrediction, Super-PRED) identified 107 juglone targets versus 1242 ovarian cancer targets (GeneCards), yielding 26 common targets via Venny. A PPI network (26 nodes, 153 edges) identified hub genes as HDAC2, CDK2, STAT3 and CDK1. GEPIA showed CDK1 overexpression with poor prognosis. Docking on HDAC2, CDK2, CDK1 produced binding energies of -7.1, -7.6 and -5.6 kcal/mol, respectively. MTT assay confirmed that juglone induced concentration-dependent cytotoxicity in OVCAR-3 ovarian cancer cells. Apoptosis and cell cycle assays demonstrated early/late apoptosis and G2/M phase arrest. Conclusion: The bioinformatics and experimental findings provide significant evidence of cytotoxic, apoptotic and cell cycle arrest properties in human ovarian carcinoma for juglone.
Keywords: Cell Cycle Arrest; Juglone; Molecular Docking; Network Pharmacology; Ovarian; Cancer